The Effect of Accountability, Transparency, and Public Participation on the Performance of Public Service Organizations (Empirical Study on Investment Board and Integrated Licensing Services in West Pasaman Regency) - G Putra, Hendra; Anita, Lili; Helmy, Herlina (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
This study aims to examine 1) The effect of accountability on the performance of public service organizations, 2) The effect of transparency on the performance of public service organizations, and 3) The effect of public participation on the performance of public service organizations. This type of research is causative research. Data was collected by distributing questionnaires directly to the respondents concerned. The data analysis technique used is multiple regression. The research findings show: 1) Accountability has a significant positive effect on the performance of public service organizations with t count > t table , namely 6.121 > 1.6608 (sig 0.000 < ? 0.05) which means H1 is accepted. 2) Transparency has a significant positive effect on the performance of public service organizations with t count > t table , namely 2.393 > 1.6608 (sig 0.019 < ? 0.05) which means H2 is accepted. 3) Public participation has a significant positive effect on the performance of public service organizations with t count > t table , namely 2.436 > 1.6608 (sig 0.017 < ? 0.05) which means H3 is accepted.